The effect of competitive actions and social media perceptions on offline car sales after automobile recalls. (February 2021) - Wang, Yen-Yao; Wang, Tawei; Calantone, Roger
Highlights: Joint effect of competitive actions and social media on car sales after recalls. The positive effect of social media on sales is amplified when the recalling firm conducts fewer competitive actions. The positive effect of social media on sales is attenuated when competitors conduct more competitive actions. Suggestions to steer through product recalls are discussed. Abstract: This paper explores the joint effect of competitive actions and social media related interactions on offline car sales after automobile recalls. Our analysis of all the mid-size automobile recall events in the U.S. from 2010 to 2015, the corresponding social media discussions of the recall and the competitive actions taken by the recalling firms and their competitors revealed that after recalls: (1) fewer competitive actions by the recalling firm are more effective in influencing car sales; (2) although social media discussions can increase awareness and sales, the change in perceptions of the brand on social media can negatively affect sales; and (3) the positive effect of social media on offline car sales is amplified when the recalling firm conducts fewer competitive actions, regardless of strategic or tactical actions, but is attenuated when competitors conduct more competitive actions. The current study adds to the competitive actions literature by considering the boundary conditions under which recalling firms can construct their competitive actions more effectively and extends the social media literature by incorporating both the focal and non-focal firms' perspectives when examining the role of social media. Managerial implications for those responsible for steering companies through product recalls are also discussed.